Gambaran Histopatologi Hati dan Ginjal Anjing Terduga Leptospirosis di Kota Denpasar (HISTOPATHOLOGICAL CHANGES OF LIVER AND KIDNEY DOG SUSPECTED CANINE LEPTOSPIROSIS IN DENPASAR CITY) - Winaya, Ida Bagus Oka; Berata, I Ketut; Kardena, I Made; Adi, Anak Agung Ayu Mirah; Rompis, Aida Louise Tenden (Jurnal Veteriner, 2018)
This study aims to determine the pathological changes in dog suspected of being infected by Leptospira spp. This research used a retrospective study design.  A total of 210 canines sample were examined at Faculty of Veterinary Medicine The Udayana of University between January 2008 to January 2010. Of the 210 specimens, five canines with clinical sign anorexia, fever, vomiting, polyurea, dyspnea and only one are noted icteric in the sclera. Macroscopically : the anemic to petechial haemorrhagis  was find in pulmo, icterus in liver with gall blader distention, kidney swollen with black color in hillus, spleen rather swollen with black color on end and mild hemorrhagis on intentines. The infected organ is inserted into a pot filled with neutral buffer formalin 10%. Then stained with haematoxyllin-eosin for the microscopic preparation. Microscopic examimination revealed  the presence of spiral bacterial cells on the necrotic liver and kidneys tissue.  Infiltration neutrophils and macrophages was also find in pulmonary and spleen tissue.  Besided that intertubuler edematous were also observed under  microscopic examination. It can be concluded changes associated with Leptospira spp infection can be found in liver and kidney tissue with changes such as necrosis, proliferation of kuffer cells and intertubular edematous.